Selective Tissue Distribution Mediates Tissue-Dependent PPARγ Activation and Insulin Sensitization by INT131, a Selective PPARγ Modulator - Xinni Xie; Xinni Xie; Xinni Xie; Wei Chen; Wei Chen; Ning Zhang; Ning Zhang; Mei Yuan; Mei Yuan; Cheng Xu; Zhibing Zheng; Zhibing Zheng; et al. (Frontiers Media S.A., 2017)
The mechanisms underlying the enhancement of insulin sensitivity by selective peroxisome proliferator-activated receptor γ modulators (sPPARγMs) are still not completely known. Here, the representative sPPARγM, INT131, was used as a probe to investigate the insulin-sensitizing mechanisms of sPPARγM in the context of tissue selective compound distribution and PPARγ regulation. First, 30 mg kg−1 INT131 was observed to produce an insulin-sensitizing effect comparable to that of 10 mg kg−1 rosiglitazone (RSG) in both db/db and DIO mice using the oral glucose and insulin tolerance tests. Similar to RSG, INT131 significantly increased brown adipose tissue (BAT) mass and adipocyte size and up-regulated the expression of BAT-specific genes. Compared with RSG, INT131 exhibited greater potency in inducing white adipose tissue (WAT) browning, decreasing adipocyte size, and increasing BAT-specific and function-related gene expression in subcutaneous WAT (sWAT). However, it did not induce hepatomegaly or hepatic steatosis, which is associated with lower levels of lipogenic genes expression. Pharmacokinetic analysis reveals that in contrast with RSG, INT131 shows higher Cmax, and much longer residency time (AUC0−12h), as well relatively lower elimination rate in adipose tissues and skeletal muscle, this demonstrated INT131 distributed predominantly in adipose tissue. Whereas, INT131 was less abundant in the liver. These results thus suggest that the tissue-selective distribution underlies INT131's selective PPARγ modulation. Compounds favoring adipose tissue may aid in development of better, safer sPPARγM to address the insulin resistance of diabetes.